Strategi Pemasaran Digital untuk Menarik Minat Wisatawan Muda ke Kawasan Desa Sawarna, Kabupaten Lebak, Banten - Rina Dwi Kristiani; Yohanes Agung Puji Triraharjo; Art Dito Pangestu; Kadek Wiweka; Budi Setiawan (International Forum of Researchers and Lecturers, 2025)
Digital marketing has become a critical element in promoting tourism destinations, particularly in attracting young tourists who are highly connected to technology. Sawarna Village in Lebak Regency, Banten, holds significant natural tourism potential, such as beaches and caves, but faces challenges in implementing promotional strategies that align with the digital behavior of the younger generation. This study employs a literature review method to analyze effective digital marketing strategies, focusing on social media, visual content, and influencer engagement. The analysis reveals that creative use of social media, a visual storytelling approach, and collaboration with micro-influencers can enhance the appeal of tourism destinations. Additionally, search engine optimization (SEO) and location-based marketing campaigns play a vital role in improving Sawarna Village's visibility on digital platforms. This study recommends digital skill training for the local community to support destination promotion and foster digital transformation in the rural tourism sector. These findings emphasize the importance of technology-driven marketing strategies to enhance the competitiveness of rural tourism destinations in Indonesia.